Using Antibiotic Game In Improving Antibiotics Knowledge: A Pilot Study In Banyumas District Women - Githa Fungie Galistiani; Alda Argyanti; Muhamad Iqbal Dikri Fadillah; Feisal Aziez; Anjar Mahardian Kusuma (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Background: The lack of antibiotic knowledge is identified as one of major problems in combating antimicrobial resistance (AMR) in Indonesia. More interactive ways added to educational tools may be more effective. Objective: This study aims to determine the impact of Focus Group Discussion (FGD) and Antibiotic Game (AG) as educational interventions in improving antibiotics knowledge among women in Banyumas District, Central Java Province, Indonesia. Methods: A quasi-experimental study with pre-/post-test design method was conducted between June–July 2023. Results: There was statistically significant difference between FGD and AG groups in improving knowledge of antibiotics in Indonesian women (p value = 0.034). Conclusion: The findings of our study will be useful for Indonesian policymakers to develop future educational interventions in improving knowledge and promoting rational antibiotic use, especially in Indonesian housewives.